The Wari occupation of Ñawinpukyo: space design, architecture and social organization in an Ayacucho community of the Middle Horizon - Leoni, Juan B. (2007)
Ñawinpukyo is generally known as one of the main sites of the Huarpa culture of the Early Intermediate Period (ca. 200 a.C. 600 d.C.) in Ayacucho. Nevertheless, recent investigations have shown that the site also has a significant Wari component that persists throughout the Middle Horizon (ca. 600 1000 d.C.). In this work, a characterization of the Wari occupation of the site is presented, underlining its specific aspects and situating it in its regional context through comparison with contemporary sites in the Ayacucho area. Although there is evidence for a cultural continuity between the Huarpa and Wari occupations of the site, it is argued that the site seems to have lost prestige and autonomy during the Middle Horizon as it was incorporated into the political-administrative structure of the Wari state in a subordinate position. Changes in spatial layout and architecture of the site, that could reflect changes in the social organization of the community, seem to be related to this broader process and are manifested in an apparent absence of the typical planned orthogonal Wari architecture and of public communal ceremonial buildings.